I am C-3PO : the inside story - Daniels, Anthony (DK Publishing, 2019)
C-3PO is one of Star Wars' most iconic characters, and Daniels is the man who knows him best. With his gleaming golden body and good-intentioned (yet worrisome) personality, the droid was there at the very beginning; he even spoke the first words uttered in any Star Wars movie. Daniels tells C-3PO's story in its entirety, from seeing the first concept images to the early stages of the final film. In the process, he tells his own story -- encounters with movie legends, the friendships he formed on-set, and the hardships, pain and in some cases real physical danger of being encased in a solid shell for countless hours. -- adapted from Amazon.com info